The Effect of Shaping Technic toward the Ability of Wearing T-Shirt for Child with Intelectual Disability - Gayatri Hardianti; M. Shodiq AM; Abdul Huda (Department of Special Education, 2017)
The objective of study is to describe skill of shirt wearing before and after intervention and describe effect shaping technique towards skill of shirt wearing for intellectual disability. Method used is single-subject research with A-B-A design. The subject was a child with intellectual disability Grade I of SDLB. Analysis of data used was and inter-condition. Results showed that the effect of shaping techniques towards skills of shirt wearing child with intellectual disability. The conclusion that there is effect shaping techniques toward skill of shirt wearing intellectual disability. Suggestions include provide learning approaches variety, parents expected to cooperate in developing independence of intellectual disability, require fundamental research.Tujuan penelitian ini adalah untuk mendeskripsikan keterampilan memakai kemeja anak sebelum dan setelah diberikan intervensi dan pengaruh teknik shaping terhadap keterampilan memakai kemeja anak tunagrahita. Metode penelitian adalah eksperimen subjek tunggal dengan desain A-B-A. Subjek adalah anak tunagrahita ringan kelas 1 SDLB. Analisis data dengan menggunakan analisis dalam kondisi dan antar kondisi. Hasil penelitian menunjukkan adanya pengaruh teknik shaping terhadap keterampilan memakai kemeja anak tunagrahita. Kesimpulan penelitian adalah terdapat pengaruh antara teknik shaping terhadap keterampilan memakai kemeja anak tunagrahita. Saran penelitian berikan variasi pendekatan pembelajaran, orang tua diharapkan bekerjasama dalam mengembangkan kemandirian anak, perlu penelitian mendasar dalam pembelajaran bina diri.DOI: http://dx.doi.org/10.17977/um029v4i12017p056